ANALISIS PREFERENSI NASABAH DALAM MEMILIH PT. BPRS BHAKTI SUMEKAR KANTOR CABANG PRATAMA GILI GENTING - Dharma Arif Maulana; Yusni Bella Mufida (Faculty of Islamic Economics and Business, 2021)
ABSTRACT Introduction: preference when choosing a banking institution to transact have a diversity of percepation. The lack of public knowledge of Islamic banking institutions is a fundamental problem for Bank Pembiayaan Rakyat Syariah (BPRS) as a sharia banking institution on the island of Gili Genting. Methods: In this study, the research design used descriptive research with a quantitative approach. The sampling technique used is the scientific sampling technique, that is , anyone who happens to meet, if it is seen that the person found is suitable as a data source. The data presented in this study include the mean, median, mode, tables, graphs, pie charts. The data analysis method used is descriptive analysis processed with SPSS. Results: The results of this study can be concluded that: First, the level of customer knowledge about the operational system of BPRS Bhakti Sumekar, Gili Genting Pratama Branch Office based on sharia principles is very good with an average value of 4.32, the information received by customers is very good with an average value the average is 4.23, and the tendency of customers' preference for BPRS Bhakti Sumekar, Gili Genting Pratama Branch Office is very good with an average value of 4.28. Second, the reasons for costumers to choose BPRS Bhakti Sumekar at the Gili Genting Pratama Branch office are very diverse, as well as the products offered, not all of them have high demand, 36% of costumers do not only transact at one bank, but have an account at another bank, and expectatons costumers for BPRS Sumekar, Gili Genting Pratama branch office so that it can be more useful for the Gili Genting Community. Conclusions and suggestions: Customer preference for BPRS Bhakti Sumekar, Gili Genting Pratama Branch Office is in the very good category with a range of scores (average between 4.20-5.00 or a score between 81%-100%). Keywords: Preference, Costumer, BPRS. ABSTRACT Introduction: preference when choosing a banking institution to transact have a diversity of percepation. The lack of public knowledge of Islamic banking institutions is a fundamental problem for Bank Pembiayaan Rakyat Syariah (BPRS) as a sharia banking institution on the island of Gili Genting. Methods: In this study, the research design used descriptive research with a quantitative approach. The sampling technique used is the scientific sampling technique, that is , anyone who happens to meet, if it is seen that the person found is suitable as a data source. The data presented in this study include the mean, median, mode, tables, graphs, pie charts. The data analysis method used is descriptive analysis processed with SPSS. Results: The results of this study can be concluded that: First, the level of customer knowledge about the operational system of BPRS Bhakti Sumekar, Gili Genting Pratama Branch Office based on sharia principles is very good with an average value of 4.32, the information received by customers is very good with an average value the average is 4.23, and the tendency of customers' preference for BPRS Bhakti Sumekar, Gili Genting Pratama Branch Office is very good with an average value of 4.28. Second, the reasons for costumers to choose BPRS Bhakti Sumekar at the Gili Genting Pratama Branch office are very diverse, as well as the products offered, not all of them have high demand, 36% of costumers do not only transact at one bank, but have an account at another bank, and expectatons costumers for BPRS Sumekar, Gili Genting Pratama branch office so that it can be more useful for the Gili Genting Community. Conclusions and suggestions: Customer preference for BPRS Bhakti Sumekar, Gili Genting Pratama Branch Office is in the very good category with a range of scores (average between 4.20-5.00 or a score between 81%-100%). Keywords: Preference, Costumer, BPRS.